Increased serum amiodarone concentration in hypertriglyceridemic patients: Effects of drug distribution to serum lipoproteins - Naoaki Hashimoto; Kosuke Doki; Satoru Kawano; Kazutaka Aonuma; Masaki Ieda; Masato Homma (Wiley, 2022)
Abstract Amiodarone and its main metabolite, desethylamiodarone (DEA), are highly distributed to serum lipoproteins such as very‐low‐density lipoprotein (VLDL) and low‐density lipoprotein (LDL), which are the carriers of triglyceride and cholesterol. This study aimed to investigate the association of serum concentrations of amiodarone and DEA with the levels of serum lipids in terms of drug distribution to lipoprotein fractions in patients with hyperlipidemia. Total serum concentrations of amiodarone and DEA were examined in 116 patients receiving amiodarone for tachyarrhythmias. The concentration‐to‐dose (C/D) ratio of amiodarone positively correlated with the level of serum triglyceride (rs = 0.541, p < 0.001) and was higher in the hypertriglyceridemic state than in normotriglyceridemic state (479 ± 211 vs. 320 ± 161, p < 0.001). No correlation was found between the C/D ratio of DEA and serum triglyceride levels (rs = 0.272), although higher values were observed in the hypertriglyceridemic state (322 ± 125 vs. 285 ± 143, p < 0.001). In the hypertriglyceridemic state, the distribution of amiodarone increased in LDL/VLDL fraction and decreased in high‐density lipoprotein and albumin fractions. The ratio of serum amiodarone to serum DEA, a metabolic ratio of amiodarone, positively correlated with serum triglyceride levels (rs = 0.572, p < 0.001) and was higher in the hypertriglyceridemic state, suggesting that amiodarone metabolism decreased in hyperlipidemia. The results of this study reveal that serum concentrations of amiodarone increase in the hypertriglyceridemic state through the increased lipoprotein‐binding and decreased metabolism of amiodarone.